Pengaruh Penambahan Sebagian Abu Daun Bambu Sebagai Filler Pada Campuran Aspal AC-WC Terhadap Karakteristik Marshall Dengan Variasi Perendaman - Palinoan, Leonardus Arnol; Nurdin, Abdul Rahim; Yunianti, Nurhadijah (Jurnal Penelitian Teknik Sipil Konsolidasi, 2023)
Asphall concrate wearing course (AC-WC) is the topmost pavement layer which functions as a wear layer. Filler function is very important to modify the gradation offine agregate in the asphall mixture so that the density increases. Asphall concrate layer (laston) is a cover layer consisting of a densely graded agregate mixture with struktural properties. The purpuse of this study was to determine the effect and variation of immersiontime on the properties and characteristics of asphal with bamboo leaf ash as part of the added material, namely 10%, 15%, and 20% with variations of immersion, 3 days, 7 days and 14 days. The number of samples of test objects made were 48 samples, with 15 normal sampels of test comparison, 27 samples of variations, 6 samples of remaining KAO. The manufacture of test specimens hot mixed and refersto the 2018test apparatus with a temperature of 60ºC and is continuedout with the marshall test to obtain stability and flow values. Based on research results and data analysis of AC-WC asphalt mixtures with the addition of 10%, 15%, 20% bamboo leaf ash, with soaking variations of 3 days, 7 days, 14 days. From the laboratory results, the addition of 20% bamboo leaf ash can increase the density, FLOW and VFB values, while a decrease occurs in the stability of VMA, MQ and VIM, but not too drastically because it is still in the specification stage